Lifestyle Factors Associated with Survival After Colorectal Cancer Diagnosis - Boyle, T.; Fritschi, Lin; Platell, C.; Heyworth, J. (Nature Publishing Group, 2013)
Background: Aside from tumour stage and treatment, little is known about potential factors that may influence survival in colorectal cancer patients. The aim of this study was to investigate the associations between physical activity, obesity and smoking and disease-specific and overall mortality after a colorectal cancer diagnosis.Methods: A cohort of 879 colorectal cancer patients, diagnosed in Western Australia between 2005 and 2007, were followed up to 30 June 2012. Cox’s regression models were used to estimate the hazard ratios (HR) for colorectal cancer-specific and overall mortality associated with self-reported pre-diagnosis physical activity, body mass index (BMI) and smoking.Results: Significantly lower overall and colorectal cancer-specific mortality was seen in females who reported any level of recent physical activity than in females reporting no activity. The colorectal cancer-specific mortality HR for increasing levels of physical activity in females were 0.34 (95% CI=0.15, 0.75), 0.37 (95% CI=0.17, 0.81) and 0.41 (95% CI=0.18, 0.90). Overweight and obese women had almost twice the risk of dying from any cause or colorectal cancer compared with women of normal weight. Females who were current smokers had worse overall and colorectal cancer-specific mortality than never smokers (overall HR=2.64, 95% CI=1.18, 5.93; colorectal cancer-specific HR=2.70, 95% CI=1.16, 6.29). No significant associations were found in males. Conclusion: Physical activity, BMI and smoking may influence survival after a diagnosis of colorectal cancer, with more pronounced results found for females than for males.